Characterization and classification of soils of Wadi Qena, Eastern Desert, Egypt - Moursy, Ali R A; El-Galil, A Abd; Ibrahim, M S; El-Hady, A A Abd; Mhalla, Bassel (The Indian Journal of Agricultural Sciences, 2020)
An investigation was carried out to characterize and classify some soils from Wadi Qena, Eastern Desert, Egypt. Twelve representative profiles were chosen based on DEM extracted from the Landsat 8 ETM+ satellite image. The soils were moderately deep to deep in depth, well drained, slightly to strongly alkaline in soil reaction (pH 7.6 – 8.4), slight to moderate saline (EC 3.3- 15.4 dS.m-1). The soils were low in organic matter (0.09 – 0.65%), low in CEC (1.5–8.1 cmol (p+).kg-1) and calcium carbonates ranged from (1.2 – 18.2%). The results revealed that the soils were low in available N (1–21 kg.ha-1), low in available P (1.0 – 9 kg.ha-1), and low to high in available K (105 – 762 kg.ha-1). Further, the soils were low in available micronutrients. Soil classification of the investigated area is done according to the field survey, morphological description and soil analyses. Two soil orders, viz Entisols and Aridisols were recognized in the study area. The soils were keyed out as Typic Torripsamments and Typic Haplocalcids at subgroup level. The obtained results can be used by decision makers to focus on prospective agricultural areas and to achieve land reclamation and better agricultural production.